Eu sou uma pessoa de tremendo sucesso': representações, identidades e trajetórias de mulheres executivas no Brasil - Andrade, Silvana Rodrigues de (2012)
The group of women that managed to break the 'glass ceiling' and reach executive positions is still small in Brazil. However, the female percentage at high level jobs in the last years is meaningfully growing in Brazil. As a relatively new phenomenon, its reflection at the academic field is not yet that expressive, and the lack of more literature about the subject makes it even harder to clearly understand the specifics of these women’s trajectory. In the face of this context, the main objective of this thesis is to ponder about the representation regarding this 'new' working woman and the elements that compose the identity of this group. Starting with analysis of 52 issues of the Vida Executiva/Mulher Executiva (Executive Life/Executive Women) magazine and 10 interviews - based on the oral history methodology - with women at executive level positions at the Brazilian professional market, we search the existing obstacles and the strategies adopted to break this 'glass ceiling' and build a career considered successful. To achieve this, we investigate the construction of an ethos to make this ascent easier, the ways found to conciliate an executive career with personal life and family and, the ideas circulating about success, work, career, maternity and family arrangements for these women.